2015
DOI: 10.1016/j.taap.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Diacetyl and 2,3-pentanedione exposure of human cultured airway epithelial cells: Ion transport effects and metabolism of butter flavoring agents

Abstract: Inhalation of butter flavoring by workers in the microwave popcorn industry may result in “popcorn workers' lung.” In previous in vivo studies rats exposed for 6 h to vapor from the flavoring agents, diacetyl and 2,3-pentanedione, acquired flavoring concentration-dependent damage of the upper airway epithelium and airway hyporeactivity to inhaled methacholine. Because ion transport is essential for lung fluid balance, we hypothesized that alterations in ion transport may be an early manifestation of butter fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 36 publications
4
23
0
5
Order By: Relevance
“…For example, it has been shown that exposure to 10 mM DA increased epithelial layer permeability as determined by decreased measures of transepithelial resistance (Fedan, Dowdy et al 2006). This observation has been supported by another study in which exposure of differentiated airway epithelial cells in air liquid interface cultures to DA for six hours at concentrations of 60 ppm and above caused a complete loss of transepithelial resistance (Zaccone, Goldsmith et al). In yet another study, it was shown that DA forms guanosine adducts (More, Raza et al 2012) that the authors state contributes to DNA uncoiling and ultimately to cell death although the mechanism by which this occurs isn’t clear.…”
Section: In Vitro Toxicitymentioning
confidence: 59%
See 1 more Smart Citation
“…For example, it has been shown that exposure to 10 mM DA increased epithelial layer permeability as determined by decreased measures of transepithelial resistance (Fedan, Dowdy et al 2006). This observation has been supported by another study in which exposure of differentiated airway epithelial cells in air liquid interface cultures to DA for six hours at concentrations of 60 ppm and above caused a complete loss of transepithelial resistance (Zaccone, Goldsmith et al). In yet another study, it was shown that DA forms guanosine adducts (More, Raza et al 2012) that the authors state contributes to DNA uncoiling and ultimately to cell death although the mechanism by which this occurs isn’t clear.…”
Section: In Vitro Toxicitymentioning
confidence: 59%
“…It is thought that because of these chemical features α-diketones including DA can affect protein structure and function as a consequence (Miller and Gerrard 2005). There are four representative in vitro studies that address the possible nature of the cellular injury that DA may cause (Zaccone, Goldsmith et al, Fedan, Dowdy et al 2006, More, Raza et al 2012, Kelly, Sun et al 2014). For example, it has been shown that exposure to 10 mM DA increased epithelial layer permeability as determined by decreased measures of transepithelial resistance (Fedan, Dowdy et al 2006).…”
Section: In Vitro Toxicitymentioning
confidence: 99%
“…The airway surface liquid and mucocilliary clearance is regulated in epithelial cells through absorption of Na+ and Cl-secretion in epithelial cells [13]. These chemicals cause disruption of the transepithelial Na+ transporters which can eventually lead to pulmonary edema [14,15], and airway obstruction [16,17]. Fedan et al, revealed transepithelial depolarization and altered tight junction integrity was adversely affected in guinea-pigs after perfusing physiological salt solution containing diacetyl into the lumen [11].…”
Section: Discussionmentioning
confidence: 99%
“…Atualmente, existe uma ampla utilização de conservantes na indústria alimentar, e alguns estudos sugerem que os aditivos tradicionais apresentam efeitos deletérios a saúde humana, em vários níveis e em diversos órgãos (ZENGIN et al, 2011;ESIMBEKOVA et al, 2017;DEHGHAN et al, 2018; (SHAN et al, 2009;KARRE et al, 2013;FALOWO et al, 2014;GIMÉNEZ et al, 2015;OSWELL et al, 2018 Certamente que a biotecnologia sustentável é o caminho para melhorar a qualidade de vida da população e ampliar o consumo de recursos naturais (PEREIRA-FREIRE et al, 2018). Outro ponto a considerar são as pesquisas com nanossistemas de encapsulamento de compostos antioxidantes e antimicrobiano que estão sendo testados para que essas substâncias sejam ativadas no alimento estendendo a validade dos produtos, além disso, embalagens comestíveis também são vistas como o próximo passo de condutas a serem tomadas e aceitas em diversos lugares (GOMEZ-ESTACA et al, 2015;VENKATASUBBU et al, 2016;ZAMBRANO-ZARAGOZA et al, 2018).…”
Section: Conservantes Naturais: Antioxidantes Antimicrobianos E Inibunclassified
“…Resultados semelhantes foram vistos com os corantes new coccine, allura red e amaranto, diferenciando-se a toxicidade em relação aos órgãos afetados e períodos de exposição analisados . Especificamente, o vermelho ponceau 4R e a camoisina causam anemia e doença renal (glomerulonefrite) e insuficiência renal e hepática, respectivamente EFSA, 2008;SILVIA, 2008;AMIN et al, 2010;EFSA, 2010 como biomarcador de exposição ambiental, cujo valor de referência é de 1,5 g de ácido hipúrico/g de creatinina e o máximo permitido é 2,5 g de ácido hipúrico/g de creatinina, além de provas de função hepática (BRASIL, 1994;KANG et al, 2005;GONZALEZ et al, 2010 FEDAN et al, 2006;KREISS et al, 2007;HUBBS et al, 2012;MORE et al, 2012;KELLY et al, 2014;ZACCONE et al, 2015;FENNELL et al, 2015;HUBBS et al, 2016 ao DNA e, eventualmente, à apoptose devido à atividade pro-oxidante (MURAKAMI, 2006(MURAKAMI, , 2007SMITH, 2009;ALAM et al, 2013). MUKHERJEE, A.; CHAKRABARTI, J.…”
Section: Corantesunclassified